2006
DOI: 10.1523/jneurosci.2279-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Terminals Independently Regulate Synaptic Clustering and Autophagy of GABAAReceptors inCaenorhabditis elegans

Abstract: Synaptic clustering of GABA A receptors is important for the function of inhibitory synapses, influencing synapse strength and, consequently, the balance of excitation and inhibition in the brain. Presynaptic terminals are known to induce GABA A receptor clustering during synaptogenesis, but the mechanisms of cluster formation and maintenance are not known. To study how presynaptic neurons direct the formation of GABA A receptor clusters, we have investigated GABA A receptor localization in postsynaptic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 61 publications
(68 reference statements)
3
117
0
Order By: Relevance
“…Interestingly, a role of autophagy in the specific degradation of GABA receptors at the neuromuscular junction has been reported. 16 Another striking observation is the presence in the embryo of numerous puncta positive for GFP::LGG-1 or GFP::LGG-2 which suggests a particular role for autophagy during embryogenesis. The massive reduction of these puncta in GFP::LGG-2(G130A) animals strongly support that they correspond to autophagosomal structures.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a role of autophagy in the specific degradation of GABA receptors at the neuromuscular junction has been reported. 16 Another striking observation is the presence in the embryo of numerous puncta positive for GFP::LGG-1 or GFP::LGG-2 which suggests a particular role for autophagy during embryogenesis. The massive reduction of these puncta in GFP::LGG-2(G130A) animals strongly support that they correspond to autophagosomal structures.…”
Section: Methodsmentioning
confidence: 99%
“…for the fi rst time reported that the cell-surface GABA A Rs, but not acetylcholine receptors, targeted to autophagosomes for degradation [49] (Fig. 1C).…”
Section: Autophagy In Postsynaptic Terminalsmentioning
confidence: 96%
“…1C). Rowland et al showed that acetylcholine receptors do not traffi c to autophagosomes in the non-innervated muscle cells of C. elegans [49] . In contrast, a recent report demonstrated that in mouse tibialis anterior muscles, autophagy contributes to the basal and atrophy-induced turnover of muscletype cholinergic receptors, nicotinic/nicotinic acetylcholine receptors in a tripartite motif containing 63 (TRIM63)-dependent manner [53] .…”
Section: In Addition To Gabars Glutamatergic N-methyl-d-aspartate Rementioning
confidence: 99%
“…EG1653 and TJ375 strains have been regularly used, respectively, to quantify the expression of UNC-49 (Abraham et al 2011;Byrd et al 2001;Garafalo et al 2015;Knobel et al 2001;Rowland et al 2006) and HSP-16.2 (Abbas and Wink 2010;Lamark and Johansen 2012;Leroy et al 2012;Rea et al 2005;Shore et al 2012;Strayer et al 2003;Wang et al 2012;Wu et al 2006) based on the quantitation of their GFP fluorescence intensities.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…This UNC-49B-GFP translational fusion protein fully rescues the uncoordinated phenotype of unc-49 (e407) and localizes to synapses. Also, GABA A receptors in C. elegans muscle cells are simple and uniform, in contrast to the structurally complex mammalian GABA A receptors (Bamber et al 1999;Gally and Bessereau 2003;Rowland et al 2006). UNC-49 receptors normally form clusters opposite inhibitory presynaptic terminals and, if this is not the case, are internalized and traffic to autophagosomes for degradation.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%